Randomized Control Trial of Postnatal rhIGF-1/rhIGFBP-3 Replacement in Preterm Infants: Post-hoc Analysis of Its Effect on Brain Injury - Horsch, Sandra; Parodi, Alessandro; Hallberg, Boubou; Malova, Mariya; Björkman-Burtscher, Isabella M.; Hansen-Pupp, Ingrid; Marlow, Neil; Beardsall, Kathryn; Dunger, David; van Weissenbruch, Mirjam; Smith, Lois E. H.; Hamdani, Mohamed; et al. (Frontiers in Pediatrics, 2020)
Background: Postnatal insulin-like growth factor-1 (IGF-1) replacement with recombinant human (rh)IGF-1 and IGF binding protein-3 (rhIGF-1/rhIGFBP-3) is being studied as a potential treatment to reduce comorbidities of prematurity. We have recently reported on a phase II, multicenter, randomized, controlled trial comparing postnatal rhIGF-1/rhIGFBP-3 replacement with standard of care (SOC) in extremely preterm infants (NCT01096784). Maximum severity of retinopathy of prematurity was the primary endpoint of the trial and presence of GMH-IVH/PHI one of the pre-specified secondary endpoints. Infants therefore received serial cranial ultrasounds scans (CUS) between birth and term age. In this post hoc analysis we present a detailed analysis of the CUS data of this trial and evaluate the effect of postnatal rhIGF-1/rhIGFBP-3 replacement on the incidence of different kinds of brain injury in extremely preterm infants Methods: This report is an exploratory post hoc analysis of a phase II trial in which infants <28 weeks gestational age were randomly allocated to rhIGF-1/rhIGFBP-3 or SOC. Serial cranial ultrasounds were performed between birth and term-equivalent age. Presence of germinal matrix hemorrhage and intraventricular hemorrhage (GMH-IVH), periventricular hemorrhagic infarction (PHI), posthemorrhagic ventricular dilatation, and white matter injury (WMI) were scored by two independent masked readers. Results: The analysis included 117 infants; 58 received rhIGF-1/rhIGFBP-3 and 59 received SOC. A trend toward less grade II–III GMH-IVH and PHI was observed in treated infants versus SOC. A subanalysis of infants without evidence of GMH-IVH at study entry (n = 104) showed reduced progression to GMH-IVH in treated infants (25.0% [13/52] versus 40.4% [21/52]; not significant). No effects of rhIGF-1/rhIGFBP-3 on WMI were observed. Conclusion: The potential protective effect of rhIGF-1/rhIGFBP-3 on the occurrence of GMH-IVH/PHI appeared most pronounced in infants with no evidence of GMH-IVH at treatment start